(untitled) (Journal of Hama University, 2022)
A total of 24 chicken muscles samples was collected from four cities in Damascus Countryside Governorate (Duma, Maraba, Nabk and Dmer). The samples analyzed for tetracycline residues (oxytetracycline, doxycycline and chlortetracycline). The tetracycline residues were determined by using HPLC technique (according to AOAC method No 995.09, 1995), with following conditions: C`18 column, mobile phase containing: acetonitrile: methanol: oxalic acid (30:10:60), 350 nm wave length, 1 mlflow rate. Results showed that 22 samples (from 24 samples) are positive for tetracycline residues (91.67%). 13 from 22 positive samples contain oxytetracycline (5 samples) and doxycycline (9 samples) residues higher than local MRL (600 µg/kg w.w), but chlortetracycline residues were lower than MRL. The changes in the oxytetracycline residues in the kidney samples were significantly differences (P<0.05) for all studded cites except the changes in oxytetracycline residues in kidney samples between Duma and Maraba and between Maraba and Nabk were not significantly differences (P>0.05). The changes in the doxycycline residues in the kidney samples were not significantly differences (P>0.05) for all studded cites except the changes in doxycycline residues in kidney samples between Duma and Maraba were significantly differences (P<0.05), The changes in the chlortetracycline residues in the kidney samples were not significantly differences (P>0.05) for all studded cites.